ANALISIS PENGARUH PENGANGGURAN, FOREIGN DIRECT INVESMENT (FDI) DAN MANUFAKTUR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA (PERIODE TAHUN 2016-2021) - Wira Ganet Aribowo (Universitas Merdeka Madiun, 2023)
Several economic theories can explain economic growth, but what is popular to explain the relevance of the relationship between economic growth, Foreign Direct Investment, Manufacturing and Unemployment is the neoclassical theory where capital flows